2010
DOI: 10.1515/znb-2010-0812
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermal Synthesis of Gallium and Indium Nitrides Using Lithium Amide

Abstract: Results of the investigation of the reactions of GaCl3, InCl3 and InI3 with LiNH2 under solvothermal conditions in benzene, which lead to metal nitrides, are reported. GaN is obtained as a cubic phase or as a mixture of cubic and hexagonal phases, depending on temperature. The effect of the addition of surfactants on the formation of GaN was explored. InN products were always contaminated with indium metal, even at low reaction temperatures. The addition of excess LiNH2 or the use of InI3 instead of InCl3 gave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, there have been just a few papers reporting the synthesis of Ga x In 1− x N nanoparticles using a scalable, mere chemical route that is also good for particles with high indium contents (for which problems with gas‐phase techniques arise because of the high volatility of In) 18. Syntheses based on metathesis reactions between lithium amide and the metal halide (of Ga or In) to prepare pure GaN and InN are known,19, 20 whereas the preparation of their alloy was not reported. Rao et al 21.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been just a few papers reporting the synthesis of Ga x In 1− x N nanoparticles using a scalable, mere chemical route that is also good for particles with high indium contents (for which problems with gas‐phase techniques arise because of the high volatility of In) 18. Syntheses based on metathesis reactions between lithium amide and the metal halide (of Ga or In) to prepare pure GaN and InN are known,19, 20 whereas the preparation of their alloy was not reported. Rao et al 21.…”
Section: Introductionmentioning
confidence: 99%
“…This has been argued as the reason why In 3+ from InI 3 is less liable to be reduced to elemental indium [13]. The reaction with InCl 3 yields InN contaminated with In metal, even at relatively low reaction temperatures of 200 • C. Chirico et al demonstrated that the use of LiNH 2 , or substituting InI 3 for InCl 3 , reduced the amount of In in the resulting products, yet did not eliminate it [32].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the synthesis of bulk crystalline InN is even more complex and tricky due to high instability of the In–N bond. In the case of profitable attempts, the reactions often occur under harsh conditions, through the use of toxic, polluting, and very hazardous reactants, such as ammonothermal growth from InCl 3 and KNH 2 in supercritical ammonia at 2.8 kbar, solvothermal reaction of InCl 3 /InI 3 with LiNH 2 in benzene, microwave plasma sources at sub-atmospheric pressure by saturating indium with nitrogen, low-temperature synthesis via nitridation of LiInO 2 or In­(OH) 3 with NaNH 2 flux in an autoclave, nitridation of In 2 O 3 and In­(OH) 3 with NH 3 at 600 °C, and solid-state exchange reaction between Ga/InI 3 and Li 3 N or InBr 3 and NaN 3 . Despite the different methods and conditions, the reactions have a very low yield, somehow producing well shaped μm-scale crystals, but rarely a pure bulk product.…”
Section: Introductionmentioning
confidence: 99%